KEPEMIMPINAN DAN KREATIF: PERAN PEMIMPIN DALAM MENGEMBANGKAN INDUSTRI KREATIF DAN BUDAYA BERBASIS INDUSTRI - Refina Dyah Pramesti Utomo Putri; Nadia Rachmawati; Mochammad Isa Anshori (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
The development of creative and cultural industries in today's digital era demands an adaptive, innovative and transformative leadership model. Leaders not only act as directors, but also as idea generators and innovation facilitators. In this context, creativity becomes an important element in leadership, as it can encourage the birth of new solutions, open space for cross-sector collaboration, and create a sustainable creative ecosystem. This article discusses the strategic role of leaders in designing creative visions, utilizing digital technology, and fostering a work culture that supports experimentation and risk-taking. It also discusses challenges such as lack of policy support and access to resources, as well as solutions through strengthening leadership education and strategic partnerships. Through an innovation-based leadership approach, creative and cultural industries can develop dynamically and contribute significantly to the nation's economic development and cultural identity.